Effects of Oral Administration of Lepidium meyenii on Morphology of Mice Testis and Motility of Epididymal Sperm Cells After Tetrahydrocannabinol Exposure - Greco, Adelaide; Del Prete, Chiara; De Biase, Davide; Palumbo, Veronica; Albanese, Sandra; Bruzzese, Dario; Carotenuto, Domenico; Ciani, Francesca; Tafuri, Simona; Meomartino, Leonardo; Mancini, Marcello; Paciello, Orlando; et al. (Frontiers in Veterinary Science, 2021)
Background: Tetrahydrocannabinol (THC) administration is associated with testicular damage and reduced semen quality. Oral administration of Lepidium Meyenii (maca) improves spermatogenesis and sperm motility and count and reduces spermatogenic damage. Objectives: The aim of this study was to evaluate the effect of administration of THC, maca, and their combination on testicular tissue and semen parameters. Materials and Methods: Thirty-six-week-old male mice were classified into control, THC, Maca, and THC + Maca groups. The mice were subjected to Eco Color Doppler ultrasound examination of the testicles before and after treatment. After euthanasia, the epididymis, testes, liver, and kidney were collected for histological examination. For morphometry of the testis, tubular diameters and seminiferous epithelium height were measured. Sperm concentration and sperm motilities were assessed. Differences among the groups were assessed using the Kruskal–Wallis and Dunn's post-hoc test. Results: In all the groups, there were no significant changes in testicular morphology before and after treatment. Histological assessment of the testes showed no alterations in control, no significant alterations in Maca, mild to moderate alterations in THC, and mild alterations in THC + Maca groups. Histological examination of the other organs showed no significant differences among the groups. Tubular diameter showed significantly increased thickening for THC and THC + Maca compared with that for Maca and control. Moreover, seminiferous epithelium height decreased for THC compared with that in the control, Maca, and THC + Maca groups. No statistically significant reduction in the spermatogenic index was observed for THC compared with that for Maca and THC + Maca. Epididymal cross-sections of the groups showed no significant alterations. Sperm concentration and motility were higher for control and THC + Maca groups than in group THC and Maca. Conclusion:In vivo maca administration reduced the deleterious effect of THC on testicular parenchyma and semen production.